Implementation of Sharia Financing Agreements with Fiduciary Submission of Property Rights to KSPPS BMT Al Hikmah Semesta - Chandra Kurniawan; Akhmad Khisni; Aryani Witasari (Sultan Agung Notary Law Review, 2021)
The research objective is to determine the role of the implementation of the Islamic financing agreement with the transfer of property rights in a fiduciary manner and how to solve the problem if there is default by the debtor, as well as the constraints and solutions in implementing the sharia financing agreement by means of musyarokah. The approach method uses empirical juridical. The data collection technique uses library research and field research. Data were analyzed descriptively qualitatively. The results of the study stated that the implementation of the sharia financing agreement with the transfer of property rights in fiduciary manner to the KSPPS BMT AL HIKMAH SEMESTA Jepara Regency consists of several stages, namely the application stage, checking and field inspection, making customer profiles, committee meetings, committee meeting decisions, binding, ordering goods consumers, payments to suppliers, collection of payments, and taking guarantee letters. The resolution of the problem if there is default by the debtor, namely given 3 warning letters if during 12 months of non-payment, and finally the guarantee will be auctioned if it is not immediately paid. Constraints and solutions in implementing the sharia financing agreement through musyarokah are document falsification by the customer, fictitious business, misuse of financing, the customer does not make payments or defaults on his obligations to the BMT according to the agreed time, BMT if there is default, namely stages that takes too long from reporting to the police to the District Court.